Comoving Distance- Light Travel Distance (Treatise) - Weitter Duckss (Budapest International Research and Critics University, 2020)
The discussion on the values of redshift, as well as blueshift, is based on a large increase in new evidence that in the whole volume of Universe there are gravitationally-bound objects (galaxies, clusters and super clusters of galaxies) „Using the Chandra and Hubble Space Telescopes we have now observed 72 collisions between galaxy clusters, including both ‘major’ and ‘minor’ mergers” (Harvey, 2015). That adds to a great diversity of galactic movement directions and their diverse appearances to an observer. The accent here is at the point of